Design Game Uwuhpoly for Improving Waste Literacy in Elementary School Children in Surabaya - Rosmiati; Rarasaning Satianingsih; Muhammad Satriawan (The Indonesian Institute of Science and Technology Research, 2026)
The low level of waste literacy among elementary school students, along with the limited availability of engaging, contextually relevant learning media, has become a major challenge in fostering early environmental awareness. This Study aimed to develop and evaluate the effectiveness of Uwuhpoly, an educational board game designed to improve waste literacy among elementary school students in Surabaya. The method R&D approach using the ADDIE model, which consists of the stages of analysis, design, development, Implementation, and evaluation. The research subjects were 142 students from Grades II to VI at an elementary school in Surabaya, selected through purposive sampling. Data were collected using waste literacy questionnaires (pretest–posttest), observation sheets, and teacher responses. Data analysis used descriptive statistical techniques and N-gain to assess improvements in students' waste literacy. The results of expert validation showed that Uwuhpoly received an average score of 4.51, indicating that the game is feasible for classroom implementation. The implementation results demonstrated a significant improvement in students’ waste literacy, with pretest–posttest score increases ranging from 35.7% to 46.7%, and an overall literacy improvement of approximately 85%. Therefore, Uwuhpoly has strong potential to be integrated into science learning (IPA), civic education (PPKn), and the Pancasila Student Profile reinforcement program as an alternative environmental literacy–based learning medium in elementary schools.